2016
DOI: 10.1155/2016/3652068
|View full text |Cite
|
Sign up to set email alerts
|

Increased Activity of the Intracardiac Oxytocinergic System in the Development of Postinfarction Heart Failure

Abstract: Aim. The present study was designed to test the hypothesis that the development of postinfarction heart failure is associated with a change of activity of the intracardiac oxytocinergic system. Methods. Experiments were performed on male Sprague-Dawley rats subjected to myocardial infarction or sham surgery. Four weeks after the surgery, blood samples were collected and the samples of the left ventricle (LV) and right ventricle (RV) were harvested for evaluation of the mRNA expression (RT-PCR) of oxytocin (OT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…OTR was localized in microvessels expressing CD31 marker and co-localized with endothelial NO synthase (eNOS) (Jankowski et al, 2010b). OTR mRNA was found in the vena cava, pulmonary veins, and pulmonary artery with lower levels in the aorta in the rats (Jankowski et al, 2000; Wsol et al, 2016). Thus, OT may modulate cardiac activity by activating OTRs on CVS.…”
Section: Atherosclerosis and Cardioprotective Effect Of Otmentioning
confidence: 96%
See 3 more Smart Citations
“…OTR was localized in microvessels expressing CD31 marker and co-localized with endothelial NO synthase (eNOS) (Jankowski et al, 2010b). OTR mRNA was found in the vena cava, pulmonary veins, and pulmonary artery with lower levels in the aorta in the rats (Jankowski et al, 2000; Wsol et al, 2016). Thus, OT may modulate cardiac activity by activating OTRs on CVS.…”
Section: Atherosclerosis and Cardioprotective Effect Of Otmentioning
confidence: 96%
“…As previously reviewed (Li et al, 2017), plasma OT levels or hypothalamic OT neuronal activities were significantly increased at the early stage of sepsis, advanced cancer patients, adjuvant arthritis and pancreatic injury, which in turn changed the activity of immune system to initiate immune defense, thereby playing the role of immune surveillance. In CVS, OT plasma levels and the activity of the intracardiac OT system significantly increased at 4 weeks after MI in the rats survived from the coronary artery ligation (Ciosek and Drobnik, 2012); post-infarction heart failure was associated with an increased activity of the intracardiac OTergic system (Wsol et al, 2016). Moreover, MI activates parvocellular OT neurons projecting to the rostral ventral lateral medulla (Roy et al, 2018).…”
Section: Atherosclerosis and Cardioprotective Effect Of Otmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the expression of the OT in the heart was described only in normotensive rats [12,23,24]. However, in our previous study, we demonstrated increased expression of OT in the hearts of rats developing post-myocardial infarction heart failure [24], where this effect was potentially associated with the antifibrogenic, antihypertrophic, anti-inflammatory effect resulting in the reduction of myocardial damage [14,15,22]. In the study by Menaouar et al oxytocin and its precursor OT-Gly-Lys-Arg (OT-GKR) blocked endothelin-1-induced cardiac hypertrophy ex vivo by activating cGMP/protein kinase G pathway and the PI3K/Akt pathway, considered essential for physiological growth but also for inhibition of pathological hypertrophy in cardiomyocytes [16,25].…”
Section: Discussionmentioning
confidence: 99%